2005
DOI: 10.1093/jmicro/dfh106
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the human periovulatory cervical mucus

Abstract: Two main types of cervical mucus have been described during the menstrual cycle: oestrogenic and progestative. Each category shows diverse morphological and functional features from the reproductive point of view. Traditionally, this change has been approached by analysing morphological patterns. In fact, a mesh model has been described for cervical mucus, structurally composed of fibrillar subunits with a parallel orientation, together with another model in a characteristic network shape with canalicular unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 35 publications
2
34
0
1
Order By: Relevance
“…Electron microscopy of human cervical mucus has produced a wide range of pore size estimates depending on the methods used, from approximately 100 nm by using SEM (10) or DMSO-mediated glutaraldehyde fixation and transmission electron microscopy (TEM) (8), to 500-800 nm by using freeze substitution and TEM (11), and even 1,000-10,000 nm or larger by using various conventional EM procedures (12)(13)(14).…”
mentioning
confidence: 99%
“…Electron microscopy of human cervical mucus has produced a wide range of pore size estimates depending on the methods used, from approximately 100 nm by using SEM (10) or DMSO-mediated glutaraldehyde fixation and transmission electron microscopy (TEM) (8), to 500-800 nm by using freeze substitution and TEM (11), and even 1,000-10,000 nm or larger by using various conventional EM procedures (12)(13)(14).…”
mentioning
confidence: 99%
“…Considering the current evidence and what has been mentioned, it is probable that the changes in hormonal levels that occur in vivo in the reproductive tract of the female of each species during the reproductive cycle subtly regulate the AR, retarding the onset or favouring its timely occurrence. As regards this delicate hormonal modulation that AR could be subject to, it is necessary to mention again the case of steroid hormones, about which more information is available: in the cervix, the oestradiol present in the periovulatory cervical mucus could be exerting the role of AR inhibitor since its onset in such regions of the female reproductive tract would not make fertilisation possible (Ceric et al, 2005;Vigil et al, 2008;Vigil et al, 2009b). On the contrary, in the distal third of the Fallopian tube, there are high levels of progesterone coming from the follicular fl uid, which could promote AR precisely when the spermatozoon and the oocyte are close to encounter, favouring successful fertilisation (Morales et al, 1992;Vigil et al, 2008;Vigil et al, 2009c).…”
Section: Discussionmentioning
confidence: 99%
“…In the physiological context of fertilisation, the spermatozoa have to migrate through the cervical mucus . This biological fl uid, found in some mammals, such as rabbits, ruminants and primates, possesses rheological properties subject to endocrine regulation, and these characteristics change in physiological and pathophysiological conditions (Vigil et al, 1991;Vigil et al, 1995;Ceric et al, 2005;Vigil et al, 2009a). After passing through the cervical mucus and endometrial cavity, the spermatozoa in the Fallopian tube come in contact with the follicular fl uid.…”
Section: Oestradiolmentioning
confidence: 99%
“…Additionally, findings from the present study suggest that the sexual hormones may influence the changes in salivary flow rate and pH during ovulation phase. Electrolyte level, pH, buffer capacity, flow rate and ultra structure have been studied in saliva in reference to several diseases and physiological conditions (26)(27)(28)(29)(30)33,(36)(37)(38)(39)(40)(41)(42). The present study revealed the difference in the electrolytes, pH, buffer capacity and flow rate of saliva during the ovulation phase.…”
Section: Discussionmentioning
confidence: 61%